A systematic review of the effectiveness of adalimumab, etanercept and infliximab for the treatment of rheumatoid arthritis in adults and an economic evaluation of their cost-effectiveness. - Chen, Y; Jobanputra, P; Barton, P; Jowett, S; Bryan, S; Clark, W; Fry-Smith, A; Burls, A (2006)
OBJECTIVES: This report reviews the clinical effectiveness and cost-effectiveness of adalimumab, etanercept and infliximab, agents that inhibit tumour necrosis factor-alpha (TNF-alpha), when used in the treatment of rheumatoid arthritis (RA) in adults. DATA SOURCES: Electronic databases were searched up to February 2005. REVIEW METHODS: Systematic reviews of the literature on effectiveness and cost-effectiveness were undertaken and industry submissions to the National Institute for Health and Clinical Excellence (NICE) were reviewed. Meta-analyses of effectiveness data were also undertaken for each agent. The Birmingham Rheumatoid Arthritis Model (BRAM), a simulation model, was further developed and used to produce an incremental cost-effectiveness analysis. RESULTS: Twenty-nine randomised controlled trials (RCTs), most of high quality, were included. The only head-to-head comparisons were against methotrexate. For patients with short disease duration (